OPTIMASI PROSES PIROLISIS PADA PEMBUATAN BRIKET BERBAHAN AMPAS BATANG TEBU DAN SEKAM PADI - Rianto Wibowo; Imam Mualiq (Universitas Muhammadiyah Semarang, 2017)
The scarcity of fuel in Indonesia and increased selling prices of fuels including kerosene, causing residents ofIndonesia's hard to get fuel. By because it was the thought of making alternative fuels derived from a mixture of bagasse and rice husks.Authors in this study will examine the variations of time and temperature pyrolysis process bagasse and rice husks. With a composition ratio of 50%: 50%. This study aims to determine the optimum conditions in the Pyrolysis process of bagasse and rice husks.The method used is to test the treatment effect of temperature and time of the pyrolysis process in order to get the results of tests according to standard ISO. Authoring process carried out at a temperature of 200 ° C, 250 ° C, 300 ° C, 350 ° C with a variation of time on hold 30 minutes, 60 minutes, 90 minutes. In order to get his test results prosimat moisture content, ash content and carbon content. Keywords: Briquettes, Proximate, Pyrolysis,